Women with hoe and pencils in hand: stories of primary teachers in the rural scope sergipano (1930-1950) - Rony Silva; Ilka Miglio Mesquita (Universidade Federal do Norte do Tocantins, 2018)
The following text seeks to understand the life stories of retired school teachers, according to their work, school, and teaching experiences. In order to do so, we analyzed stories collected from sixteen previously-interviewed teachers, considering the early-twentieth century policy of feminization in this profession and, subsequently, the abandonment of the countryside populace, which in turn left them to their own devices, keeping them away from educational improvements, this being the product of heavy investment on the urbanization model going on in the country at the time. However, schools in the countryside and their teachers played, in this regard, and in spite of the precariousness of its facilities and of the overall training of its teachers, an important role in institutionalizing of Sergipe's primary school.